IbM Pelatihan Formulasi Sabun Padat Susu Kambing - Uswatun Chasanah; Dyah Rahmasari; Mutiara Titani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Training has been held on the formulation of goat milk solid soap to the community. The partners of this activity are a group of fresh Ettawa goat milk producing communities who live in the village of Torongrejo, Klerek, Batu city. The training process for goat milk solid soap formulation begins with a lecture on solid soap formulation, then proceed with a workshop on making goat milk solid soap. The achievement of this activity is an increase in knowledge as well as the skills of the Partners regarding the formulation and manufacture of goat milk solid soap.